Administrator Observation and Feedback: Does It Lead Toward Improvement in Inquiry-Oriented Math Instruction?. (August 2017) - Rigby, Jessica G.; Larbi-Cherif, Adrian; Rosenquist, Brooks A.; Sharpe, Charlotte J.; Cobb, Paul; Smith, Thomas
Purpose: This study examines the content and efficacy of instructional leaders' expectations and feedback (press) in relation to the improvement of middle school mathematics teachers' instruction in the context of coherent systems of supports.Research Method/Approach: This mixed methods study is a part of a larger, 8-year longitudinal study in four large urban school districts across the United States. We used transcripts of interview data, surveys, and video recordings of instruction of 271 cases, over 4 years, to determine the content of administrator press, as reported by teachers, and the relationship between the content and change (if any) in instruction. To do so we used qualitative coding of interview transcripts, and ran a series of statistical models to examine the nature of the variance in and impact of administrative press.Findings: Most of the administrators' press, as reported by teachers, was not targeted toward specific teachers' mathematics instruction in ways that would likely lead toward improvement in those practices. Rather, the press focused on content-neutral instructional practices or classroom management and organization.Implications for Research and Practice: The instructional leadership practice of administrator observation and feedback is widespread, yet understudied as it relates to changes in teacher practice. Our findings indicate that current policies that mandate principals to spend substantial time in classrooms are unlikely to result in significant improvements in the quality of instruction unless meaningful resources are invested to support administrator learning.